A Case of Repeat Kidney Transplant Intolerant to Multiple First-line Immunosuppressive Agents Mycophenolate Mofetil, Azathioprine, and Calcineurin Inhibitors - Puneet Arora; Rajan Duggal; Deepak Garg; Tarique Naseem (Indian Journal of Transplantation)
A repeat kidney transplant is the preferred treatment for graft failure due to its enhanced survival benefits and improved quality of life, despite facing greater medical, immunological, and surgical challenges compared to the first transplant. Immunosuppressive medications are indispensable for organ recipients to prevent rejection and prolong the viability of transplanted organs. At present, triple-drug therapy comprising calcineurin inhibitors, corticosteroids, and antiproliferative medications is the prevailing protocol for immunosuppressive treatment in renal transplant recipients. In conjunction with the intended therapeutic outcomes, the administration of immunosuppressive agents entails the potential for specific adverse reactions. This patient developed chronic diarrhea due to mycophenolate mofetil, severe bone marrow suppression with azathioprine due to thiopurine methyltransferase enzyme deficiency, and developed thrombotic microangiopathy with tacrolimus, despite maintaining recommended therapeutic drug levels, leading to the withdrawal of all three drugs. The case highlights the need for newer immunosuppressive drugs and protocols that are more effective and less toxic.